Comparison of H2S adsorption by two hydrogel composite (HBC) derived by Empty Fruit Bunch (EFB) biochar and Coal Fly Ash (CFA) - Meri, Nor Hidayah; Alias, Azil Bahari; Talib, Norhayati; Rashid, Zunaira; Wan Ab. Karim Ghani, Wan Azlina (IOP Publishing, 2018)
This study are covered the adsorption performance of two adsorbent Empty Fruit Bunch Hydrogel Biochar Composite (EFB-HBC) and Coal Fly Ash Hydrogel Composite (CFA-HC) on hydrogen sulphide. The EFB biochar were produce by pyrolysed and heated from room temperature to 550˚C at 10˚C/min under the Nitrogen flow. Meanwhile, coal fly ash collected from a power plant located in Selangor, Malaysia. Both of the materials is a waste from different industries and became the precursor to our adsorbents. EFB biochar and coal fly ash has been synthesized to become hydrogel by polymerization process with acrylamide (AAm) as monomer, N,N'-methylene bisacry lamide (MBA) as cross linker and ammonium persulfate (APS) as initiator. In addition, because of the speciality of hydrogel itself, which is has high ability in storing water, the effect of H2O wetness on EFB-HBC and CFA-HC were investigate in adsorption of H2S. EFB-HBC gave a longest breakthrough time and highest adsorption capacity compared with CFA-HC in both condition (dry/wet). The result also indicated that, the increased the bed height, increased the adsorption capacity.